A Representative Survey of Knowledge, Use, Perceived Benefits, Barriers, and Risks of Select Herbal Drugs Among Female Students in Gorgan City (Northeast Iran) - Mohammad R. Ghanbari MSc; Elham Lotfalinezhad MSc; Elahe Lotfalinezhad MSc; Devender Bhalla PhD (SAGE Publishing, 2017)
We conducted a representative survey among young women to determine knowledge, use, and perceptions on barriers, benefits, and risks related to selected herbal drugs ( Crocus sativus , Borago officinalis , Citrus aurantium , Thymus vulgaris , Matricaria chamomilla , Lavandula angustifolia , Valeriana officinalis , Hypericum perforatum , and Panax ginseng ) in Gorgan by using an internally validated questionnaire. There were 344 participants (mean age 16.3 years; 16.2% in science course). Saffron had most reported knowledge (n = 265, 77.0%) and ever use (n = 324, 94.1%). The average number of source of knowledge was 2.5; parents (n = 224, 65.1%) were the single most frequent source. Media (combined magazine, the Internet, TV, radio) was the source of knowledge for 283 (82.2%) participants. Actual use was "harmful" for the majority (n = 182, 52.9%; no idea n = 83, 24.1%). Parents and media provided knowledge on herbal drugs for most, supporting unsurprisingly high perceived knowledge but harmful actual experience. Programs to educate people are needed to not take herbal drugs lightly.